Some Remarks on a Multi Point Boundary Value Problem for a Fractional Order Differential Inclusion - Cernea, Aurelian (Journal of Applied Nonlinear Dynamics, 2026)
We study a multi point boundary value problem for a fractional order differential inclusion involving a nonconvex set-valued map. We establish a Filippov type existence theorem and we prove the arcwise connectedness of the solution set of the problem considered.